The Role of Company Size, Company Value, and Liquidity in Capital Structure of Food and Beverages Companies - Jayanti Mandasari (Komunitas Dosen Indonesia, 2024)
The equilibrium that occurs between long-term debt and equity is referred to as the capital structure, and it is a component of the financial structure. The financial structure includes the capital structure as one of its components. When attempting to determine the optimal composition of a company's capital structure, it is absolutely necessary to take into consideration the presence of variables that have an effect on the capacity of the capital structure. This study's objective is to explore the impact that company size, company value, and liquidity have on the capital structure of the company so that appropriate action can be taken. Panel data are utilized in the research that was carried out, which is quantitative in nature. For the purposes of this investigation, the population is comprised of all Food and Beverage companies that were listed on the Indonesia Stock Exchange between the years 2019 and 2023. One form of sampling method that is utilized for the selection of samples is known as purposeful sampling. Thirteen businesses were chosen to serve as research samples after being chosen according to a set of criteria that had been established beforehand. The data that was utilized in this investigation was secondary data, which was gathered from the IDX in the form of financial reports of businesses that are involved in the provision of food and beverages throughout the period of 2019-2023. The approach of multiple linear regression analysis was utilized for the aim of conducting data analysis in this particular investigation. The results show that, at least partially and concurrently, the size, value, and liquidity of a company have a major impact on its capital structure.